The Feasibility Analysis and Risk of Patchouli Farming Production in Aladadio Village Aere District East Kolaka Regency - Megawati Megawati; Weka Gusmiarty Abdullah; Wa Ode Yusria (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2023)
This study aims to analyze the feasibility and risks of patchouli farming production. The study was conducted in Aladadio Village, Aere District, East Kolaka Regency. The location of the study was determined intentionally or purposively with the consideration that the study location was one of the villages whose main livelihood was as patchouli farmers. The population in this study was all patchouli farmers in Aladadio Village, which amounted to 174 households. At the same time, the number of respondents was 35 patchouli farmers, who were taken simply by random sampling. Variable research includes production, receipts, revenue, fixed costs, variable costs, total costs, RC ratio, sources of risk, frequency of risk events, risk events, quantitative impacts, qualitative impacts, risk levels, and risk management efforts. The first data analysis technique uses RC Ratio calculation analysis. Frequency x Impact is used to determine the risk and risk level of patchouli farming and risk management efforts using descriptive analysis. The results showed that the RC Ratio obtained was 1.53, which means that every 1 unit spent by farmers for patchouli farming costs will result in revenues of 1.53 units because the RC Ratio value is greater than 1, patchouli farming is still feasible to cultivate. The source of risk in farming is found in land management, planting, maintenance, harvesting, and post-harvest with a calculation of frequency x impact to produce a number 4 or the level of risk in patchouli planting, which is a high level. Efforts to manage production risks are carried out by avoiding risks so that the risk of planting does not occur sustainably. The highest risk is caused by climate/weather, where the risk avoidance method is by paying attention to the patchouli plant seeds used. If patchouli seedlings are taken from patchouli plants that have diseases, then when planting, it is most likely that patchouli is challenging to grow. Besides, weather and climate conditions are also very influential. When planting is carried out in the rainy season, it can produce good results. Still, if the weather conditions are hot, the number of deaths in the crop will be higher, so farmers plant patchouli by cutting to avoid the mortality rate in patchouli plants.